2017
DOI: 10.1161/jaha.117.007244
|View full text |Cite
|
Sign up to set email alerts
|

Very Late Pathological Responses to Cobalt–Chromium Everolimus‐Eluting, Stainless Steel Sirolimus‐Eluting, and Cobalt–Chromium Bare Metal Stents in Humans

Abstract: BackgroundThe “very late” clinical outcomes for durable polymer drug‐eluting stents and bare metal stents (BMSs) have been shown to be dissimilar in clinical studies. Conceptually, the long‐term vascular compatibility of BMSs is still regarded to be superior to drug‐eluting stents; however, no pathologic study to date has specifically addressed this issue. We evaluated the very late (≥1 year) pathologic responses to durable polymer drug‐eluting stents (cobalt–chromium [CoCr] everolimus‐eluting stents [EESs] an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
2
25
0
1
Order By: Relevance
“…Although polymer on the first-generation DES and biodegradable polymer of BES could evoke inflammation, high biocompatibility of durable polymer on the EES led to low inflammation at early phase after EES implantation. Mori et al reported that EES demonstrated the least inflammation near-equivalent healing to bare-metal stent and low neointimal formation [24]. Although the drug on the EES is almost released within the first 3 months after implantation, this low inflammation led to a small increase in neointimal thickness from 3 to 12 months, and this neointimal growth did not compromise the lumen area within the stent from our present study.…”
Section: Vascular Reactions and Vessel Healing After Ees Implantationsupporting
confidence: 60%
“…Although polymer on the first-generation DES and biodegradable polymer of BES could evoke inflammation, high biocompatibility of durable polymer on the EES led to low inflammation at early phase after EES implantation. Mori et al reported that EES demonstrated the least inflammation near-equivalent healing to bare-metal stent and low neointimal formation [24]. Although the drug on the EES is almost released within the first 3 months after implantation, this low inflammation led to a small increase in neointimal thickness from 3 to 12 months, and this neointimal growth did not compromise the lumen area within the stent from our present study.…”
Section: Vascular Reactions and Vessel Healing After Ees Implantationsupporting
confidence: 60%
“…In fact, a previous pathological study demonstrated even worse inflammatory responses to cobalt-chromium BMS than to everolimus-eluting stents. 32 If a metal induces atherosclerotic changes after the drug effect has stopped, the amount of metal, represented by size and length of the stent, may have an effect on the development of neoatherosclerosis, as shown in the present study.…”
Section: Discussionsupporting
confidence: 53%
“…One study evaluated very late (1–5 years) pathological response to EES (EES; Abbott Vascular) and BMS (Multilink Vision; Abbott Vascular). A lower inflammatory response of the EES was observed concerning the BMS platform [ 45 ]. The pathology findings translated into better clinical outcomes in the EXAMINATION trial that included 1498 patients with STEMI [ 46 ].…”
Section: Discussionmentioning
confidence: 99%